Development of an Interactive Website as an Information and Product Ordering Medium for Raja Konveksi Engineering Aceh MSME - Farabi, Fadlal Ramadhan; Mik Salmina; Ully Muzakir (LPPM Politeknik Aceh Selatan, 2026)
This study focuses on the development of an interactive website designed to function as an information and product ordering medium for Raja Konveksi Engineering Aceh MSME. This research was conducted in response to the absence of an official online platform, where promotional activities and product orders were previously handled manually through photo sharing and direct communication, resulting in limited efficiency and reach. The system was developed using the Waterfall method, encompassing requirement analysis, system design, implementation, testing, and maintenance stages. The website was built using PHP with the CodeIgniter framework, supported by a MySQL database, and integrated with HTML, CSS, JavaScript, and Bootstrap to enhance interactivity and responsiveness. System evaluation was carried out through a user satisfaction questionnaire involving 25 respondents. The findings indicate a satisfaction rate of 95.52%, categorized as very high. This result demonstrates that the developed website effectively supports information delivery and online product ordering. The implementation of this system is expected to strengthen digital promotion, broaden market access, and improve the efficiency of the ordering process for Raja Konveksi Engineering Aceh.